New Methods for Robotic Perception by Using in-Air Sonar Data. (26th February 2016) - Giannoccaro, Nicola Ivan; Spedicato, Luigi
In recent years, the authors studied the possibility of using low frequency in-air ultrasonic sensors in several applications of robotic interest related to the perception and the reconstruction of the external environment. They introduced several methods based on innovative mathematical tools for solving problems, such as the position detection and orientation of a mobile robot with respect to a corridor wall, the correct reconstruction of two orthogonal panels in spite of the effect of multiple reflections affecting the data in the corner zone, and the reconstruction of the boundary walls of a room environment. All the proposed innovative strategies were tested on a designed mechatronic scanning system consisting of ultrasonic sensors rotated by a servo modular actuator and also with the data from a scanning validated model. In this review, the main steps and achievements will be presented so as to summarize the research work of recent years as well as reflect on the importance of appropriate and innovative techniques regarding ultrasonic data processing. The originality of the present work concerns the possibility of disposing all the developed approaches as a whole in order to use in-air ultrasonic sensors for robotic perception in several environmental situations.